2021
DOI: 10.1039/d1em00094b
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, sources and exposure risk of polycyclic aromatic hydrocarbons in soils, and indoor and outdoor dust from Port Harcourt city, Nigeria

Abstract: In this study, we evaluated the concentrations, composition, sources, and potential risks of polycyclic aromatic hydrocarbons (PAHs) in soils, and indoor and outdoor dust from Port Harcourt city in Nigeria....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 130 publications
3
8
0
Order By: Relevance
“…Despite the differences in the analytical approach, number of PAHs analyzed, and climatic conditions, such a comparison provides information on global concentration trends. The PAH concentrations in the indoor dust from these areas were higher than those reported for indoor dust from rural, semi-urban and urban areas in Nigeria 28,30,33,34 and other regions, 22,24,27,45 but were comparable to those found for indoor dust from Warri, Nigeria 30 and Changchun, China. 22 The PAH concentrations in the outdoor dust from these rural communities were higher than those previously reported for similar matrices from the Niger Delta and other parts of Nigeria 6,31,32,34–36 and some cities with diverse anthropogenic pressures in other regions, 20,23,25,26,47–49 but were lower than those of outdoor dust from Ulsan, Korea.…”
Section: Resultssupporting
confidence: 64%
See 3 more Smart Citations
“…Despite the differences in the analytical approach, number of PAHs analyzed, and climatic conditions, such a comparison provides information on global concentration trends. The PAH concentrations in the indoor dust from these areas were higher than those reported for indoor dust from rural, semi-urban and urban areas in Nigeria 28,30,33,34 and other regions, 22,24,27,45 but were comparable to those found for indoor dust from Warri, Nigeria 30 and Changchun, China. 22 The PAH concentrations in the outdoor dust from these rural communities were higher than those previously reported for similar matrices from the Niger Delta and other parts of Nigeria 6,31,32,34–36 and some cities with diverse anthropogenic pressures in other regions, 20,23,25,26,47–49 but were lower than those of outdoor dust from Ulsan, Korea.…”
Section: Resultssupporting
confidence: 64%
“…The PAH concentrations in the indoor dust from these areas were higher than those reported for indoor dust from rural, semi-urban and urban areas in Nigeria 28,30,33,34 and other regions, 22,24,27,45 but were comparable to those found for indoor dust from Warri, Nigeria 30 and Changchun, China. 22 The PAH concentrations in the outdoor dust from these rural communities were higher than those previously reported for similar matrices from the Niger Delta and other parts of Nigeria 6,31,32,34–36 and some cities with diverse anthropogenic pressures in other regions, 20,23,25,26,47–49 but were lower than those of outdoor dust from Ulsan, Korea. 17 Kong et al 50 reported PAH concentrations of 1410 to 54 780 μg kg −1 in dust from the Dongying oilfield in China, which were lower than the PAH concentrations in dust from OTJ but were higher than those of EBD and EME.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…Different methods have been used to determine the possible sources of contamination, with which prevention plans can be established, with chemometrics (set of statistical methods) being the most prominent [8]. Among the main chemometric methods are Cluster Analysis (CA) which allows classifying elements or variables [9][10][11][12], and Principal Component Analysis (PCA) that makes possible to summarize the variables to a smaller set and, likewise, facilitates the identification of pollution sources [13][14][15][16][17][18][19]. In order to relate geographic information with pollutants concentration in difficult-to-reach areas, the spatial representation of pollution phenomena has been used.…”
Section: Introductionmentioning
confidence: 99%